Розчини бензолсульфонату літію в диметилсульфоксиді як електроліти для літієвих хімічних джерел струму - Присяжний, В.Д.; Сіренко, В.І.; Потапенко, О.В.; Змієвська, Т.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The electrochemical characteristic of solutions of lithium salts (perchlorate, tetrafluoroborate, and trifluoromethylsulfonate) in dimethylsulfoxide is considered. The conductivities of solutions are determined. The electrochemical stability area of solutions is in the interval 4.5–4.6 V. Electrochemical properties of lithium manganese oxide spinel in the tested solutions are investigated. The charge-discharge capacity of lithium manganese oxide spinel is 61 mA·h/g (in the interval of potentials from 3.2 to 4.4 V Li/Li+) and 190 mA·h/g (in the interval of potentials from 2.0 to 4.0 V Li/Li+) for vanadium oxide (V).